Contribute of Behaviorism: Optimizing Skinner's Principles for Prosocial Character and SDG 16 in Primary Education - Nazli Nahrowi; Alivia Rizky Wulan Santoso; Nabilah Kenza Putri Anwariyah (Universitas Negeri Surabaya, 2025)
The problems of deviant behavior and low discipline among elementary school students remain a challenge in creating a conducive learning environment. Most previous studies have focused more on cognitive aspects, while the dimension of prosocial character and its contribution to Sustainable Development Goals (SDGs) 16 has not been widely studied. This study aims to analyze the application of reinforcement principles (positive and negative reinforcement) and shaping behavior in shaping the discipline and prosocial behavior of elementary school students, as well as to explain its contribution to the achievement of SDG 16 through peaceful and inclusive education. This study uses a qualitative approach with a library research method. Data were obtained from various academic literature such as reputable journals, books, and research reports relevant to B.F. Skinner's operant conditioning theory. Data analysis was conducted using descriptive qualitative methods through the stages of reduction, categorization, and interpretation of literature to find patterns of correlation between behavioral reinforcement and character building in students. The results showed that consistent reinforcement increased students' intrinsic motivation, self-discipline, and social responsibility, while shaping behavior played a role in gradually forming prosocial behavior. The new findings from this study produced a conceptual model of Behaviorism-Contributive, which is the integration of Skinner's theory with social-emotional values relevant to the context of Indonesian primary education. Theoretically, this model broadens the neo-behavioristic perspective in education, while practically, it can be used as a reference for teachers and educational institutions to create a peaceful, inclusive, and equitable learning ecosystem in line with SDG 16.